Baohe pill decoction for diarrhea induced by high-fat and high-protein diet is associated with the structure of lactase-producing bacterial community - Zhou, Kang; Deng, Na; Yi, Xin; Cai, Ying; Peng, Maijiao; Xiao, Nenqun (Frontiers in Cellular and Infection Microbiology, 2022)
Background: This study investigated the effects of Baohe pill decoction on the diversity and community composition of lactase bacteria in the intestinal contents of mice with diarrhea induced by high-fat and high-protein diet, which provided an experimental basis for the study on the therapeutic mechanism of Baohe pill decoction. Materials and methods: The Traditional Chinese Medicine Systems Pharmacology (TCMSP), DisGeNET, UniProt, National Center for Biotechnology Information (NCBI), and GeneCards databases were used to collect the related targets with active ingredients of Baohe pill decoction, diarrhea, and lactase, and then construct correlation networks. Fifteen Kunming mice were randomly divided into the control group (CN), natural recovery group (NR), and Baohe pill decoction treatment group (BHP), with five mice in each group. After constructing a mouse diarrhea model by HFHPD induction, BHP was gavaged with Baohe pill decoction, and the other groups were gavaged with distilled water of equal. The intestinal contents were collected from ileal to jejunal and analyzed using metagenomic sequencing to characterize the intestinal content of lactase-producing bacteria in mice. Results: The core active components related to diarrhea in Baohe pill were quercetin, luteolin, kaempferol, forsythin, and wogonin. And there was no intersection between the related targets with the active ingredient of Baohe pill, lactase, and diarrhea. After the intervention of Baohe pill decoction, the Observed species, Chao1 index, and Operational Taxonomic Units (OTU) number increased in BHP (P > 0.05), while the Pielous evenness and Shannon index decreased (P > 0.05). In Beta diversity, the community structure of the NR was significantly different from CN and BHP (P < 0.05), and the community structure of the CN was not significant difference from BHP (P > 0.05). Compared to NR, the relative abundance of Bifidobacterium and Amycolatopsis increased, while the relative abundance of Lachnoclostridium, Sinorhizobium, Cedecea, and Escherichia decreased in BHP, but none of the significant differences (P > 0.05). Conclusion: The therapeutic effect of Baohe pill decoction on diarrhea induced by HFHPD does not appear to involve the body's lactase gene targets directly, but is associated with the change of the construction of lactase-producing bacterial communities.